2020
DOI: 10.1002/adfm.202000647
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase‐Like Nanozymes Induce a Novel Form of Cell Death and Inhibit Tumor Growth In Vivo

Abstract: Nanomaterials with intrinsic enzyme-like properties, termed nanozymes, have attracted significant interest, although limited information is available on their biological characteristics in cells or in vivo. Here, it is shown that nanomaterials with peroxidase-like activity trigger a novel form of cell death through an ATP-citrate lyase (ACLY)-dependent rat sarcoma viral oncogene (RAS) signaling mechanism. The peroxidase nanozyme-induced cell lethality, which is termed as nanoptosis, is morphologically and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…This previous study and this study all revealed that the treatment of Fe 3 O 4 nanoparticles induced lipid accumulation in cells. In consistence with the previous study [ 36 ], this study also found that several lipid synthesis-related genes were upregulated in HF, including FDFT1, ACAT2, and HMGCS1. In contrast, the most significant biological process was myeloid leukocyte activation and cation homeostasis in the PBNP-treated HL60 cells ( Figure 4 C,D).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This previous study and this study all revealed that the treatment of Fe 3 O 4 nanoparticles induced lipid accumulation in cells. In consistence with the previous study [ 36 ], this study also found that several lipid synthesis-related genes were upregulated in HF, including FDFT1, ACAT2, and HMGCS1. In contrast, the most significant biological process was myeloid leukocyte activation and cation homeostasis in the PBNP-treated HL60 cells ( Figure 4 C,D).…”
Section: Resultssupporting
confidence: 90%
“…This gene was also upregulated in HF and HP. This kind of significant effect of FeNPs on lipid metabolism was also found in the HepG2 cell treated by Fe 3 O 4 nanoparticles in a previous study [ 36 ]. This previous study and this study all revealed that the treatment of Fe 3 O 4 nanoparticles induced lipid accumulation in cells.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Since the discovery of first iron-containing nanozyme in last decade 4 , numerous nanomaterials have been elucidated to have oxidase 5 , catalase 6 , SOD 7,8 , peroxidase 9 , monooxygenase 10 , hydrolase 11 , laccase 12 mimicking activities and therefore been used in diverse applications like the destruction of biofilm, removal of algal bloom, immunoassay, tissue staining, cancer treatment, and glucose biosensing. However, despite being the most promising candidate as catalytic biomedicine, the clinical translation of nanozymes for therapeutic usage is still lacking [13][14][15] . Inherent toxicity of the materials used in the preparation of contemporary nanozymes, low aqueous solubility, inability to properly function in the physiological milieu, lack of selectivity (towards biological substrate), and incompatibility with other enzymes in catalyzing intracellular cascade reactions are considered to be the confounding factors [15][16][17][18] .…”
Section: Main Textmentioning
confidence: 99%
“…Combination of the observed behavioral features indicated that the anxiety was induced due to severe 3-NPA neurotoxicity, which was ameliorated upon treatment with C-Mn 3 O 4 nanozymes. Light [12] preference test was further used to validate our observations about the anxiolytic effects of replaced with a novel object, and the animals were permitted another 2 mins of exploration [13] time. Their time of interaction with each of the two objects were measured during the experimental period (Supplementary Figure S6a).…”
Section: Main Textmentioning
confidence: 99%